Media portrayal of Child marriage in Nigeria in the light of existing laws - Worugji, Nheoma Eme (Department of Public Law, 2019)
Child marriage is a union between two persons of which one or both of the parties is less than the age of 18. The practice or phenomenon of child marriage cuts across countries, cultures, religions and ethnicities from Africa to Asia, Europe and America. From the perspective of legislation and human rights, it is a menace and a violation of the rights of the child. Unfortunately, the category of children adversely affected are the females and is associated with parents giving out their girl child who are less than 18 years of age in marriage to men who are far older than they are. Topmost on the list of drivers or reasons for perpetuating such practice is that when the girl child gets married at such an early age, the prospect of being promiscuous is taken away with no regard to the aftermath health implication of such action. Nigeria is one of the countries with a high prevalence of child marriage cutting across all ethnicities with major occurrences in the Northern part of the country. The Child Rights Act which was passed into law in Nigeria in 2003 expressly criminalises the practice and pegged the age for marriage at 18 in line with international standards and the African regional treaties. The Nigerian print media has also taken the cue to bring to the lime light issues of child rights violation and associated harmful practices. However, there seems to be an unseen discussion in relation to the role and influence of the media and its portrayal of the issue in the light of existing laws and solution required to address the surrounding issues. This is what this research sets out to explore. The objective is to investigate multiple debates and perspectives of child marriage as presented in Nigerian newspapers. The research method employed is document analysis and discourse analysis which will take the form of documentary research.